A study of the improvement of academic burnout of students with different learning styles by teacher-student collaborative assessment - Jiang, Yong; Ge, Wen-ting; Wu, Yu-ge; Zhou, Han-zhu; Zhang, Jun-xuan (Frontiers in Psychology, 2025)
IntroductionAcademic burnout has become a pressing concern in higher education, particularly with the rise of online learning. This study aimed to investigate the effectiveness of the Teacher-Student Collaborative Assessment (TSCA) model in mitigating academic burnout among college students with diverse learning styles.MethodsA quasi-experimental design was applied to two undergraduate classes (n = 85) at Jilin Medical University. The Kolb Learning Style Inventory was used to categorize students into adaptive, assimilative, divergent, and convergent types. Academic burnout was assessed at the start and conclusion of a 3-month TSCA-based course using a validated burnout questionnaire.ResultsThe results indicated that students with adaptive and divergent learning styles experienced a statistically significant decrease in burnout levels (P < 0.05), whereas those with assimilative and convergent styles did not (P>0.05).DiscussionThese findings suggest that the TSCA model may be particularly effective for certain learner types in reducing academic burnout and enhancing engagement in online education. This study provides practical insights for personalized teaching interventions and online course design.